THE KETOGENIC DIET VS. CIVILIZATIONAL DISEASES: A REVIEW OF ITS APPLICATIONS IN DIABETES, ALZHEIMER’S DISEASE, AND ONCOLOGY - Paulina Redel; Kamila Prusinowska; Aleksandra Dzwonkowska; Lidia Jasińska; Marta Bronikowska; Karolina Michalczuk (International Journal of Innovative Technologies in Social Science, 2025)
The ketogenic diet (KD) - a high-fat, low-carbohydrate, and moderate-protein diet - is gaining increasing recognition as a potential strategy to help treat a variety of conditions, including cancer, type 2 diabetes, and neurodegenerative diseases such as Alzheimer’s. KD’s mechanisms of action are mainly based on inducing a state of ketosis, in which the body switches from using glucose to ketone bodies as its main energy source. Cancer remains one of the world’s most serious public health problems, and the effectiveness of current anti-cancer therapies is still sometimes limited. As a result, there is a growing interest in methods that support treatment, including nutritional interventions. The ketogenic diet (KD), based on high-fat intake, low carbohydrate intake, and moderate protein intake, shows potential as an adjuvant therapeutic strategy for cancer treatment. KD can affect the metabolism of cancer cells by increasing oxidative stress and reducing glucose availability, making cancer cells more susceptible to chemotherapy and radiotherapy, while protecting healthy cells. The ketogenic diet has been used with great success for more than 100 years to alleviate the course of many serious neurological diseases. The rapidly increasing number of patients suffering from obesity and type 2 diabetes in recent years has forced the search for new, effective ways to reduce body weight. The use of the ketogenic or low-carbohydrate diet in this context is of increasing interest to both physicians and the general public. This review presents current evidence from preclinical and clinical studies on the anticancer properties of the ketogenic diet, including its effects on tumor growth, angiogenesis, immune response, and the inflammatory environment. In addition, the use of KD in the treatment of other conditions, such as diabetes and Alzheimer’s disease, is discussed. Although the diet is widely used clinically and has shown promising results in treating many pathologies, further research is needed on its long-term safety, especially in the context of cardiovascular risk. The article also provides an overview of the mechanisms of action of KD and possible side effects resulting from its use.